PENGARUH DISIPLIN DAN MOTIVASI TERHADAP KINERJA KARYAWAN PADA PT. JALUR NUGRAHA EKAKURIR PEKANBARU - Faizah, Henny Anatta Hafizatul; ", Kasmiruddin (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
This study aims to determine how much the influence of discipline and motivation on employee performance. Samples in this study were taken as many as 46 respondents and the technique used is Total Sampling. The data in this study used a survey method through a questionnaire filled out by employees. Data obtained using simple regression analysis and multiple regression analysis.             The results of this study indicate that discipline has a significant effect on employee performance. Motivation has a significant effect on employee performance. And simultaneously discipline and motivation have a significant effect on employee performance. Future studies are suggested to use other methods in examining employee performance, for example through in-depth interviews with respondentsKeywords:  Dicipline, Motivation, Employee Performance